Fear of Injections and Needle Phobia Among Children and Adolescents: An Overview of Psychological, Behavioral, and Contextual Factors - Tage Orenius; LicPsych; Hanna Säilä MD, PhD; Katriina Mikola MD; Leena Ristolainen DSc, PT (SAGE Publishing, 2018)
The purpose of this clinical update is to provide an overview of the fear of needles and needle phobia in children and adolescents including characteristics and diagnosis, prevalence and epidemiology, etiological factors, and treatment options. Needle-related fear and needle phobia present as significant needle-related distress and avoidance behavior. The etiology is biopsychosocial. These challenging conditions are more common in children and adolescents than in adults. The nurse-patient relationship enables the provision of suitable preparation before injection procedures. Nurses can use exposure-based interventions and incorporate coping strategies and teaching of parents and children. Nurses play a pivotal role in noticing the need for further treatment. Procedural needle-related distress is a complex phenomenon representing a continuum ranging from needle fear to more severe needle phobia. For patients with needle fear management and training methods used by nurses can possibly prevent a progression of the condition into needle phobia. In cases of needle phobia, a correct diagnosis made by a psychiatrist is necessary and enables referral to a psychotherapist with experience in treating children and adolescents with needle phobia.